2016
DOI: 10.1152/ajprenal.00455.2015
|View full text |Cite
|
Sign up to set email alerts
|

Late intervention with the small molecule BB3 mitigates postischemic kidney injury

Abstract: Ischemia-reperfusion-mediated acute kidney injury can necessitate renal replacement therapy and is a major cause of morbidity and mortality. We have identified BB3, a small molecule, which when first administered at 24 h after renal ischemia in rats, improved survival, augmented urine output, and reduced the increase in serum creatinine and blood urea nitrogen. Compared with control kidneys, the kidneys of BB3-treated animals exhibited reduced levels of kidney injury molecule-1, neutrophil gelatinase-associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Ace inhibition can limit kidney damage in this transplant model (Noris et al, 2003), which has also been used to assess the development of alloimmunity (de Heer et al, 1994), the efficacy of immunosuppressants (Chandraker et al, 1998), non-immune therapies (Magee et al, 1999) and the development of fibrosis in the graft (Jain et al, 2000). The small molecule BB3 is a hepatocyte growth-factor mimetic, and studies in an IRI-induced rat model of AKI revealed that BB3 protected the kidney from tubular apoptosis and necrosis (Narayan et al, 2016). These data form the basis of a clinical trial using BB3 in kidney-transplant recipients who present with delayed graft function.…”
Section: Renal Transplantationmentioning
confidence: 99%
“…Ace inhibition can limit kidney damage in this transplant model (Noris et al, 2003), which has also been used to assess the development of alloimmunity (de Heer et al, 1994), the efficacy of immunosuppressants (Chandraker et al, 1998), non-immune therapies (Magee et al, 1999) and the development of fibrosis in the graft (Jain et al, 2000). The small molecule BB3 is a hepatocyte growth-factor mimetic, and studies in an IRI-induced rat model of AKI revealed that BB3 protected the kidney from tubular apoptosis and necrosis (Narayan et al, 2016). These data form the basis of a clinical trial using BB3 in kidney-transplant recipients who present with delayed graft function.…”
Section: Renal Transplantationmentioning
confidence: 99%
“…In vivo studies have shown that it binds to renal c-Met receptors, producing the same decreases in apoptosis and increases in proliferation induced by endogenous HGF. In a series of pre-clinical studies, Narayan et al 38 induced renal ischemia reperfusion injury in rats and randomized animals to receive 2 mg/kg of ANG-3777 or placebo at 24 hours after injury. Compared to vehicle, ANG-3777 reduced tubular epithelial apoptosis preserving nephron mass, and also reduced hemorrhage, tubular dilation, and acute tubular necrosis.…”
Section: The Role Of Hepatocyte Growth Factor and Ang-3777 In Renal Rmentioning
confidence: 99%
“…Additionally, animals treated with ANG-3777 showed increased urine output, decreased SCr and blood urea nitrogen, and reduced mortality. 38 In a phase 2 randomized placebo-controlled double-blind proof-of-concept study in renal transplantation patients showing signs of delayed graft function (a form of AKI in kidney transplantation), patients treated with ANG-3777 showed improvements in multiple endpoints compared to placebo. ANG-3777–treated patients had higher urine output over 28 days after transplantation, lower SCr, higher estimated glomerular filtration rate (eGFR) up to 1 year, greater reduction in markers of renal damage (C-reactive protein and neutrophil gelatinase-associated lipocalin), and shorter duration of dialysis and transplant hospitalization.…”
Section: The Role Of Hepatocyte Growth Factor and Ang-3777 In Renal Rmentioning
confidence: 99%
“…BB-3, produced by Angion Biomedica Corporation, is a small molecule with HGF- like activity. In preclinical trials, BB-3 given 24 hours after ischemic injury mitigated AKI, as evidenced by lesser changes in urine output, creatinine, and BUN, reduced urinary KIM-1 and NGAL excretion, and showed less tubular apoptosis and necrosis on histopathology [53]. In the interim analysis of a multicenter Phase II study in renal transplant patients with low or no urine output post-transplant, those patients who received 3 doses of BB-3 had increased urine output, lower serum creatinine, and reduced need for dialysis (NCT01286727).…”
Section: Repair Agentsmentioning
confidence: 99%